Faktor-Faktor yang Mempengaruhi Harga dan Penggunaan Lahan di Sekitar Jalan Lingkar Salatiga - Rusdi, Muhamad (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Development Salatiga quite rapidly both in terms of population growth, level of activity level and urban physical development requires the availability of adequate transportation infrastructure. To anticipate the problems that may arise and to develop the suburban areas built Ring Road Salatiga (JLS). This study aims to analyze the factors that affect the land price and land use around JLS as well as its association with the development of the city. The selection of study variables using rank analysis, Relative Rank Index (RRI) and the factors that influence was analyzed by spearmans correlation. The results obtained show that the price of land around JLS ranged between Rp 200.000,00 – Rp 2.000.000,00 per meter too far above NJOP price that ranges between Rp 20.000,00 – Rp 537.000,00 each meter. Land Use arround of JLS dominated by trade in services (56.52%) and the trend of land conversion that happens is to trade in services (79.82%). Changes in land use is influenced by two factors namely accessibility and land prices. The existence of JLS directly provide space for the development of new growth suburbs Salatiga and increase physical development of the city in the form of land up 10.8 ha in the period 2010-2012 year.